(untitled) (Journal of Bio-Science, 2019)
This study aims to find out the present environmental status and issues that have emerged in the recent time due to change in human activities, resource extraction and human dependency on the forest. This study is based on both qualitative and quantitative approach with Participatory Rural Appraisal (PRA) tools and random sampling of 260 respondents, six focus group discussions (FGDs), six key informants interviews (KIIs). The result suggests that about 90% of poor and middle-classhouseholds are depended on the income from tourism, agriculture or boat riding activities. Both the local people and tourists’activities are responsible for decreasing environmental condition by plastic pollution, land cover and land use change, water follows control, road and building construction and violence of rules and regulation. The south and east boundaries, and the center of the forest are mainly facing land use and land cover changes between the years of 2005 to 2018. For sustainable management, local communities should be aware of the importance of swamp forest and have to find out alternative income sources to reduce pressure on swamp forest in terms of resources extraction and forest degradation. J. bio-sci. 28: 51-57, 2020